THE INFLUENCE OF ENTREPRENEURSHIP ASPECTS ON THE SUCCESS OF THE CHIPS INDUSTRY IN MATANG GLUMPANG DUA AND PANTON PUMP - Rahmaniar, Rahmaniar; Subhan, Subhan; Saharuddin, Saharuddin; Nur Ilham, Rico; Anwar, Khairil (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2022)
This study aims to identify the effect of business location on the income of the pulse kiosk business in Lhokseumawe City and to identify the effect of business capital on the pulse kiosk business income in Lhokseumawe City. The number of samples in this study were 68 respondents who were determined using saturated sampling (census). The type of data used is primary data collected using research questionnaires. Data analysis used multiple linear regression equations with SPSS 20 tools. The results showed simultaneously Fcount > Ftable or 33,649 > 3,138, the conclusion was that business location and business capital had a significant effect on the income of pulse kiosks in Lhokseumawe City. Based on the results of the partial test, it is known that for the business location variable the value of tcount > ttable or 3.945 > 1.997, and the operating capital variable tcount > ttable or 2.484 > 1.997, it can be concluded that partially the business location and business capital have a significant effect on the income of pulse kiosks in Lhokseumawe City. The business location variable is the dominant factor affecting the income of the pulse kiosk in Lhokseumawe City. The author's suggestion for pulse kiosk business owners is that indicators of business location and business capital must be increased in order to be able to increase their pulse kiosk income. The author's suggestion to further researchers is to develop other independent variables that are considered capable of influencing business income. it can be concluded that partially the business location and business capital have a significant effect on the income of the pulse kiosk in Lhokseumawe City. The business location variable is the dominant factor that affects the income of the pulse kiosk in Lhokseumawe City. The author's suggestion for pulse kiosk business owners is that indicators of business location and business capital must be increased in order to be able to increase their pulse kiosk income. The author's suggestion to further researchers is to develop other independent variables that are considered capable of influencing business income. it can be concluded that partially the business location and business capital have a significant effect on the income of the pulse kiosk in Lhokseumawe City. The business location variable is the dominant factor affecting the income of the pulse kiosk in Lhokseumawe City. The author's suggestion for pulse kiosk business owners is that indicators of business location and business capital must be increased in order to be able to increase their pulse kiosk income. The author's suggestion to further researchers is to develop other independent variables that are considered capable of influencing business income.